Aguila o sol - Cantinflas, 1911-1993; Aguila, Guz; Arvide, Manuel; Barriero, Luis G., 1886-1947; Boytler, Arcady, 1893-1965; Medel, Manuel, 1906-; Mier, Felipe; Mora, Margarita, 1920-; Tamayo, Marina (Divisa Ediciones, 2002)
Para todos los públicos.